2011
DOI: 10.1172/jci57761
|View full text |Cite
|
Sign up to set email alerts
|

Nod2 sensing of lysozyme-digested peptidoglycan promotes macrophage recruitment and clearance of S. pneumoniae colonization in mice

Abstract: Streptococcus pneumoniae colonizes the mucosal surface of the human upper respiratory tract. A colonization event is gradually cleared through phagocytosis by monocytes/macrophages that are recruited to the airway lumen. Here, we sought to define the bacterial and host factors that promote monocyte/macrophage influx and S. pneumoniae clearance using intranasal bacterial challenge in mice. We found that the recruitment of monocytes/macrophages required their expression of the chemokine receptor CCR2 and correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
205
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(217 citation statements)
references
References 74 publications
10
205
1
1
Order By: Relevance
“…In contrast to this positive regulation of RANTES by type I IFNs, two recent studies showed that type I IFNs negatively regulate KC and CCL2 production in an influenza/S. pneumoniae coinfection model (57,58). Collectively, type I IFNs appear to regulate differentially various proinflammatory mediators during infections in the lung, possibly depending on the magnitude of production and on the infection conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to this positive regulation of RANTES by type I IFNs, two recent studies showed that type I IFNs negatively regulate KC and CCL2 production in an influenza/S. pneumoniae coinfection model (57,58). Collectively, type I IFNs appear to regulate differentially various proinflammatory mediators during infections in the lung, possibly depending on the magnitude of production and on the infection conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the inhibitory effect of poly-ICLC and IFN-ÎČ was not seen in macrophages from Ifnar -/-mice. We had previously shown that the CCL2 response to S. pneumoniae was NF-ÎșB-dependent and required sensing of peptidoglycan by Nod2 (17). To examine directly the inhibitory effect of poly-ICLC and IFN-ÎČ on Nod2 signaling, we used HEK293T cells transfected with a Nod2-expressing plasmid or empty vector control and NF-ÎșB reporter plasmid.…”
Section: Figurementioning
confidence: 99%
“…The decline in the bacterial load requires the influx of monocytes/macrophages into the airway lumen (15). Recruitment of these cells correlates with the expression of the chemokine CCL2 and is deficient in mice lacking its receptor, CCR2, which is also required for early clearance (15,17). Recognition of pneumococci by pattern recognition receptors TLR2 and Nod2 - which sense lipid-modified constituents and muramyl dipeptide-containing (MDP-containing) peptidoglycan fragments, respectively - contributes to the production of CCL2, the influx of macrophages, and bacterial clearance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Toll-like receptor (TLR) members TLR2 and TLR9 detect pneumococcal cell wall components and CpG-rich DNA, respectively [9][10][11]. Among NOD-like receptors (NLRs), NOD2 recognizes pneumococcal peptidoglycan and NLRP3 is activated by PLY [12][13][14][15]. Moreover, AIM2 as well as another STING-dependent cytosolic DNA sensor detect pneumococcal nucleic acid in the host cell cytosol [7,12].…”
Section: Introductionmentioning
confidence: 99%